The Influence Of Service Quality And Customer Satisfaction Towards Customer Loyalty At Bank Mega Syariah Bengkulu - Afif Fakhri Pahlevi; Suwarni Suwarni; Nurzam Nurzam (Penerbit Jurnal Indonesia, 2021)
The purpose of this study is to determine the influence of service quality and customer satisfaction on customer loyalty at Bank Mega Syariah Bengkulu. The sample in this study was 93 main savings customers at Bank Mega Syariah, Bengkulu City. The sampling technique was accidental sampling technique. Data were collected using a questionnaire and analyzed through multiple linear regression, test of determination and hypothesis testing. The results of the regression analysis show Y = 12.730 + 0.303X1 + 0.410 X2, this shows a positive direction of regression, meaning that there is a positive influence between X1 (service quality) and X2 (customer satisfaction) on customer loyalty (Y). This means that if the variable service quality and customer satisfaction increases, it will increase customer loyalty. The coefficient of determination is 0.399. This means that X1 (service quality) and X2 (customer satisfaction) affect customer loyalty (Y) by 39.9%, while the remaining 59.1% is influenced by other variables not examined in this study. The results of the t test at the 0.05 significance level explain that partially the variable service quality and customer satisfaction have a significant influence on the customer loyalty variable of Bank Mega Syariah Bengkulu. The results of the F test at the 0.05 significance level explain that the variables of service quality and customer satisfaction have a simultaneous (joint) influence on customer loyalty at Bank Mega Syariah Bengkulu.